The impact of a managerial overconfident narrative on capital structure decisions - Barbosa, Tiago Emanuel Monteiro (2019)
Capital Structure, which consists on the financing mix used by corporations in order to maximize their value, represents one of the most controversial topics on the corporate finance field. Despite the innumerous studies on this topic there is not yet a consensual theory on what is the ideal capital structure a firm should adopt. As a consequence, a stream of research began to apply psychological and social based conventions in order to focus on the aspect that can possible help decode the capital structure puzzle: The cognitive and behavioral biases that influence the decision-making process. This empirical study intends to examine the relationship between the overconfidence bias and the capital structure decisions. The sample comprises UK non-financial firms from 2004 and 2014 and the variables that will proxy for the overconfidence were adapted from Alves et al. (2016). The results provide evidence of a negative relation between overconfidence and debt levels. Similar results were obtained for different specifications on the dependent and independent variables.